Pengenalan Budaya Provinsi Jawa Barat sebagai Pembelajaran Siswa SDN Sepang Kota Serang - Ratna Dewi; Ismail Pahmi; Ratu Bilqis Nurhaida; Serly Opriyana; Wulan Oktavia (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
West Java is a province rich in history, culture, and traditions that form an essential part of Indonesia's national identity. Culture-based education plays a strategic role in shaping the character and cultural appreciation of younger generations toward the nation's heritage. This study employs a qualitative approach by introducing elements of West Javanese culture to students at SDN Sepang, Serang City, through visual learning media. The visuals depict cultural elements such as Jaipong dance, Wayang Golek puppetry, Angklung musical instruments, traditional clothing, and regional cuisine. The findings indicate that visual media effectively enhances students' interest and understanding of local culture while fostering a sense of pride and love for cultural heritage. The pedagogical approach, inspired by the Montessori method, offers students the freedom to explore, thereby promoting creativity and independence in learning about culture. This cultural learning not only preserves traditional values but also serves as a means of social transformation in addressing the challenges of globalization. The study emphasizes the importance of integrating local culture into the formal education curriculum, the need for teacher training, and community involvement to support sustainable cultural education. Therefore, culture-based education can serve as a strong foundation for cultivating knowledgeable, culturally-rooted, and character-driven future generations, contributing to sustainable national development.